PROFILE OF UNIVERSITY PROFESSORS: A STUDY IN THE STATE OF TOCANTINS (Fiep Bulletin - online, 2010)
The study object of our research was to identify the professional profile of academic staff of the City of palms, state of Tocantins. From this question we define the general objective of this research to identify, through the proposed variables, the professional profile of academics from institutions of higher education in the city of Palmas - Tocantins. We develop a field research that showed characteristics associated with exploratory research descriptive method. We follow the route of quantitative survey research technique, using an instrument (questionnaire) to identify the profile of the university faculty, consisting of variables relating to gender, age, area of operation, degree of schooling, teaching full time ; time teaching in higher education, length of service at current institution, the weekly working hours; exercise another activity. The sample included 194 teachers who teach in higher education in Palmas - TO and integrate the staff of six higher education institutions different. After analyzing the data, we found that the university professor de Palmas - TO is a man or a woman who is aged between 31 and 40 years old, is professor of private institution of higher education, works in the area of Human Sciences , is an expert or master, has between 7 and 18 years of professional experience is in the process of experimentation and diversification in higher education serves for a period between seven and eighteen years, working between five and eight hours daily in the teaching and the two five hours outside of teaching.